Secure data management 4th VLDB Workshop, SDM 2007, Vienna, Austria, September 23-24, 2007 : proceedings - SDM (Workshop) (Lecture notes in computer science, 2007)
Although a number of cryptography and security techniques have been around for quite some time, emerging technologies, such as ubiquitous computing and ambient intelligence that exploit increasingly interconnected networks, mobility and personalization, put new requirements on privacy and security with respect to data management. As data are accessible anytime anywhere, according to these new concepts, it becomes much easier to get unauthorized data access. As another consequence, the use of new technologies has brought some privacy concerns. It becomes simpler to collect, store, and search personal information and endanger people’s privacy. Therefore, research in the area of secure data management is of growing importance, attracting the attention of both the data management and securityresearch communities. The interesting problems range from traditional topics, such as access control and general database security, via privacy preserving data mining, to new research directions, such as search on encrypted data and privacy-enhancing technologies. This year, the call for papers attracted 29 papers both from universities and industry. For presentation at the workshop, the Program Committee selected 11 full papers (37% acceptance rate) as well as 4 position papers. These papers are also collected in this volume, which we hope will serve you as a useful research and reference material. Access control -- A unified conflict resolution algorithm -- Multi-layer audit of access rights -- Refinement for administrative policies -- Database security -- Authenticating kNN query results in data publishing -- Query rewriting algorithm evaluation for XML security views -- Answering queries based on imprecision and uncertainty trade-offs in numeric databases -- Architecture for data collection in database intrusion detection systems -- Common secure index for conjunctive keyword-based retrieval over encrypted data -- Privacy protection -- Generating microdata with P-sensitive K-anonymity property -- Preventing privacy-invasive software using collaborative reputation systems -- Towards improved privacy policy coverage in healthcare using policy refinement -- Positon papers -- Requirements of secure storage systems for healthcare records -- An intrusion detection system for detecting phishing attacks -- A three-dimensional conceptual framework for database privacy -- Novel RFID authentication schemes for security enhancement and system efficiency.